Effect of physiological age of stem and IBA treatment on rooting of branch cuttings of Taxus baccata L. - Das, Saumitro; Jha, L.K. (Current Botany)
The natural population of Taxus baccata L. (Himalayan Yew) throughout the Indian Himalayan Region is greatly reduced due to its extensive and reckless exploitation for “Taxol” an anticancer drug. The effects of overexploitation are exacerbated by the species poor regeneration process, slow growth rate and prolonged seed dormancy. Therefore vegetative propagation by branch cuttings seems to be only practical solution for its large scale multiplication. A study was conducted on six candidate trees (CTs) to examine the effect genotype, physiological age of stem, IBA treatment on rooting of Taxus baccata cuttings. Results revealed that rooting behaviour of cuttings was significantly affected by all the factors under study. Among the six CTs studied, CT 2 (from BSI, Shillong) had given the highest rooting response (46.28%). The juvenile cuttings have the higher rooting capacity; however the callusing was more prominent in mature cutting. The influence of IBA treatment was also significant for rooting where 1000 was most effective for stimulating rooting juvenile cuttings and 2000 ppm in mature cuttings.